Child Sacrifice in Ancient Israel - Dewrell, Heath D. (Book collections on Project MUSE., 2022)
Among the many religious acts condemned in the Hebrew Bible, child sacrifice stands out as particularly horrifying. The idea that any group of people would willingly sacrifice their own children to their god(s) is so contrary to modern moral sensibilities that it is difficult to imagine that such a practice could have ever existed. Nonetheless, the existence of biblical condemnation of these rites attests to the fact that some ancient Israelites in fact did sacrifice their children. Indeed, a close reading of the evidence--biblical, archaeological, epigraphic, etc.--indicates that there are at least three different types of Israelite child sacrifice, each with its own history, purpose, and function.In addition to examining the historical reality of Israelite child sacrifice, Dewrell's study also explores the biblical rhetoric condemning the practice. While nearly every tradition preserved in the Hebrew Bible rejects child sacrifice as abominable to Yahweh, the rhetorical strategies employed by the biblical writers vary to a surprising degree. Thus, even in arguing against the practice of child sacrifice, the biblical writers themselves often disagreed concerning why Yahweh condemned the rites and why they came to exist in the first place.